PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT SINAR SANTOSA PERKASA CIKARANG - Arni Kurniati dan Elia Rossana Dewi Sartika (Fakultas Ekonomi Universitas Borobudur, 2016)
The research aims to examine and analyze the influence of leadership style, motivation and work discipline toward performance of employee in PT Sinar Santosa Perkasa Cikarang. Data collection sample of 69 respondents Santosa Sinar Perkasa PT Cikarang given questionnaires and selected probability sample with sampling gradual withdrawal method (multistage sampling). Analysis of the data in this study using SPSS version 21.The results were obtained from the regression equation as Y = a + b1x1 + b2X2 + b3X3. This equation means that every increase of 1 scores leadership style variable (X1) effect on employee performance variable (Y) of 0.855, assuming motivation variable (X2) and discipline (X3) is constant.Any change in one variable score of motivation (X2) effect on employee performance variable (Y) of 0.613, assuming a leadership style variable (X1) and discipline (X3) is constant. Any change in one variable score work discipline (X3) influence on employee performance (Y) amounted to 0,600, assuming a leadership style variable (X1) and motivation (X2), is constant. Keywords: Leadership style, Motivation, Work Discipline and Employee Performance